Selectivity Index of Alpinia galanga Extract and 1’-Acetoxychavicol Acetate on Cancer Cell Lines - Da'i, Muhammad; Meilinasary, Khairunnisa Azani; Suhendi, Andi; Haryanti, Sari (Indonesian Journal of Cancer Chemoprevention, 2019)
Previous research stated that galangal (Alpinia galanga) extract has a potential as cytotoxic agent with active compound of 1’-Acetoxychavicol Acetate (ACA). The objective of this study was to determine the selectivity of ethanol extract, ethyl acetate fraction, and methanol fraction of of galangal, and ACA on cancer cell lines. Cytotoxic activity was carried out using the MTT method on T47D breast cancer, WiDr colon cancer, HeLa cervical cancer, and Vero normal cell lines. The results showed that galangal ethanol extract and its fractions had selectivity index equal to or less than 2 on cancer cells. Meanwhile, ACA had selectivity index more than 3 on T47D cell and HeLa cell. ACA showed a strong cytotoxic activity against cancer cells T47D, HeLa, and WiDr with IC50 values of 3.14, 7.26, and 12.49 μg/ml, respectively. Based on data, it could be concluded that ACA was the most selective to inhibit T47D cell with a selectivity index of 6.6.Keywords: 1’-Acetoxychavicol acetate, galangal (Alpinia galanga), selective index, cytotoxic